Peranan Komoditas Jagung terhadap Perekonomian Wilayah Kabupaten Karo - MILALA, SELLY PRASANTA BR; AMBARAWATI, I GUSTI AGUNG AYU; DEWI, RATNA KOMALA (Jurnal Agribisnis dan Agrowisata (Journal of Agribusiness and Agritourism); Vol.12, No.1, Juli 2023, 2023)
Analysis of the Role of Corn Commodities in the Economy of the Karo Regency Corn is one of the world's most important food crops, besides wheat and rice. Karo Regency has the highest corn production in North Sumatra Province.The purposes of this study are (1) to examine whether corn is a basic commodity in Karo Regency; (2) to analyze Karo Regency's revenue from corn; and (3) to examine the role of corn in the economy of Karo Regency. This research is descriptive and quantitative. This research was conducted in Karo Regency. This research uses secondary data. Data collection is done by documentation and analyzed using Location Quotient, Dynamic Location Quotient, Shift Share, and Acceptance methods. The results showed that corn is a basic commodity with a value of LQ > 1 and will remain a basic commodity in the future with a value of DLQ > 1. Karo Regency's revenue from corn commodities from the year of observation fluctuated, namely in 2016 it decreased by 11% and increased in 2017 by 18%. In 2018, it again decreased by 6% and experienced a fairly large increase in 2019, which was 29%. Corn commodities in Karo Regency have an important role in the economy of the Karo Regency area, including opportunities to increase people's purchasing power for processed corn products, both for food and feed products. The Karo Regency government can provide necessary counseling and assistance to farmers to increase corn commodity production in Karo Regency, which, in the end, can increase the wealth or ability of Karo Regency to carry out regional development.